Evaluación técnico financiera de la incorporación de citrus paradisi (pomelo) en una cerveza artesanal tipo sour ale para la empresa Slava (2021)
The increase in small and medium-sized companies entering the craft brewery industry has led to greater competitiveness in the sector, forcing microbreweries to create new flavors that attract consumer attention. Among these microbreweries is Slava SAS, a company that seeks to offer the customer a different sensory experience, by adding fruit extracts, cocoa, among others, in its production process.